The impact of organizational justices on organizational success: the mediating role of organizational citizenship behavior - Besfat Engdaw; Melaku Kebede (Cogent Social Sciences)
Success is the ultimate end that any organization is looking for, regardless of the nature of the organization. A variety of factors in occupational settings affect organizational success. Employees’ perception of fairness with regard to organizational practices can have an important implication on the success of the organization. The purpose of this study is to examine the influence of organizational justice on organizational success, monitoring the mediating role of organizational citizenship behavior. Primary data collected from a total of 328 Amhara Regional State Public Enterprises employees were used to test the proposed relationship between the constructs of the study. Correlation and multiple regression data analysis techniques were employed. Structural Equation Modeling was used to run a mediation analysis. Findings revealed that organizational justice has a significant positive effect on their success (β = 0.45, p < 0.01). The study also confirmed that organizational citizenship behavior has a statistically significant effect on organizational success (β = 0.308, p < 0.01). The finding of the mediation analysis indicated that organizational citizenship behavior partially mediates the relationship between organizational justice and success. Finally, the study recommends public enterprises promote organizational justice and citizenship behavior.